2013
DOI: 10.1185/03007995.2013.792247
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between background cancer pain, breakthrough pain, and analgesic treatment: a preliminary study for a better interpretation of epidemiological and clinical studies

Abstract: Vol. 29, No. 6, 2013, 667-671 The different operational definitions of breakthrough cancer pain (BTcP) has generated unclear epidemiological data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 23 publications
1
38
0
2
Order By: Relevance
“…According to a prevalent definition, breakthrough pain (BTP) is a transitory exacerbation of pain, severe in intensity and with a rapid onset, superimposed on an otherwise stable pain pattern in patients treated with opioids [1][2][3] . The presence of BTP has been considered as a negative prognostic factor, and influences the quality of life of these patients 4 .…”
Section: Introductionmentioning
confidence: 99%
“…According to a prevalent definition, breakthrough pain (BTP) is a transitory exacerbation of pain, severe in intensity and with a rapid onset, superimposed on an otherwise stable pain pattern in patients treated with opioids [1][2][3] . The presence of BTP has been considered as a negative prognostic factor, and influences the quality of life of these patients 4 .…”
Section: Introductionmentioning
confidence: 99%
“…From a clinical point of view, this gray area of moderate pain is commonly considered as needing a better analgesia. It has been reported that such range of pain intensity significantly interferes with daily activity and that mild pain should be considered at least ≤4/10 on a numerical pain scale [7,8]. Thus, the differences between the intensity of BTcP could be minimal (1-2 points on a numerical scale).…”
Section: Definition and Epidemiologymentioning
confidence: 98%
“…For instance, clear differences have been found between very advanced cancer patients followed at home and unselected patients recruited in an oncologic setting, like those observed in this study [6,7]. Thus, breakthrough pain should be considered as a dynamic entity dependent on several factors, including analgesic treatment, level of physical activity, and the course of disease [8].…”
mentioning
confidence: 48%